Silicone Septum Leakage at the Origin of a Drug Overdose in a Patient Implanted With an Intrathecal Pump. Issue 5 (25th October 2012) - Perruchoud, Christophe; Bovy, Michèle; Rutschmann, Blaise; Durrer, Anne; Buchser, Eric
<x xml:space="preserve">Abstract</x> Introduction Intrathecal (IT) pump failures usually result in decreased drug administration and symptom reoccurrence with or without withdrawal syndrome. We report a case of a leaking silicone septum associated to a systemic drug overdose. Case Report An 84‐year‐old patient treated with IT clonidine for chronic back pain presented with a state of confusion, visual hallucinations, and hypertension two hours after an unremarkable pump (SynchroMed EL, Medtronic, Minneapolis, MN, USA) refill. The reservoir was emptied and 14 mL (8.4 mg of clonidine) was found to be missing (difference between retrieved and expected volumes). The pump was refilled and a check on the next day showed again a loss of 3.5 mL. A malfunction was suspected and the pump was replaced (SynchroMed II, Medtronic). The inspection of the external surface of the pump revealed severe damage to the silicone septum with multiple gouges due to needle scarring. A fluid leak also was clearly seen through the septum. Discussion The signs and symptoms presented by this patient are consistent with clonidine overdose that resulted from a combination of a possible accidental pocket fill and a definite septum leak into the subcutaneous tissue. The damage to the silicone could be due to the loss of the nontraumatic properties of the Huber needles that are rubbed against the metallic case in attempting to locate the injection port during refill procedures. Conclusion This observation is the first description of a silicone septum damage contributing to a pump dysfunction and drug overdose despite the use of appropriate needles for refilling.